Nonagenarians qualify for total knee arthroplasty: a report on 329 patients from the Swedish Knee Arthroplasty Register 2000–2016 - Sezgin, Erdem A; Robertsson, Otto; W-Dahl, Anette; Lidgren, Lars (Acta Orthopaedica, 2018)
Background and purpose — The nonagenarian (those aged 90 years and older) population is expected to double in the next 20 years. This demographic age quake may have a significant impact on the incidence of total knee arthroplasty (TKA), although current literature provides limited data. We examined death and revision rates, patient-reported outcomes (PROs) and bias on patient selection of nonagenarian patients operated on with TKA for osteoarthritis (OA) between 2000 and 2016. Patients and methods — The Swedish national knee arthroplasty register was used to identify 329 nonagenarians (mean age, 92 years). Each patient was followed-up until death or the end of 2017. PRO data of 22 of these patients were compared with 65- to 74-year-old patients operated in 2015, from the same register. Results — 5 patients (1.5%) died within 90 days and 23 (7%) patients died within 365 days after TKA. 8 patients (2.4%) developed knee complications that needed revision. For patients followed for 5 and 10 years, more than 50% and 10%, respectively, lived without being revised. The patients had statistically significant improvements in PROs, not significantly different from the younger SKAR cohort. However, the material is small and this statistical finding does not preclude that there may be clinically relevant differences. TKA incidence was different amongst the 21 counties in the country (range, 0–5.1/10,000). Interpretation — Our study suggests that nonagenarians with knee OA qualify for TKA, having similar outcomes to younger patients. The data presented may help surgeons and patients assessing the risks and outcome associated with the procedure.